Предмет: Алгебра,
автор: 12947Sunny
(x+3)^2-7(x+3)=0 решить уравнение
Ответы
Автор ответа:
3
(x+3)²-7(x+3)=0
x²+6x+9-7x-21=0
x²-x-12=0
D=(-1)²-4*1(-12)=1-(-48)=1+48=49=7
x1=(1-7)/(2*1)=-6/2=-3
x2=(1+7)/(2*1)=8/2=4
Ответ:x=-3;x=4
12947Sunny:
спасибо!
Автор ответа:
0
Ответ:
Объяснение:
(x+3)^2-7(x+3)=0
x²-x-12=0
D=-1²-4*1*(-12)=49
x1=(√49-(-1))/(2*1)=4
x2=(-√49-(-1))/(2*1)=-3
Похожие вопросы
Предмет: Литература,
автор: anastasiaignatcik9
Предмет: Химия,
автор: sabi0000
Предмет: Математика,
автор: jaroslavaaaaa
Предмет: Математика,
автор: веснлина
Предмет: Математика,
автор: qamidovaa